Relación entre recaudación tributaria e inversión pública en el Perú, durante el periodo 2017 - 2019 - Pezo Aquino, Junior Alexis (2022)
The purpose of the study was to analyze the relationship between the levels of tax collection and public investment in Peru between 2017 and 2019. For this, quantitative analyzes were carried out, using descriptive statistics and inferential statistics, through a semi-logarithmic econometric regression model. linear for panel data. Our results show that public investment in Peru has a positive relationship with tax collection, more specifically if tax collection increases by 10%, public investment will increase by approximately 5.3%. We also conclude that, given our results, we can validate our hypotheses, both general and specific, since we demonstrate quantitatively that public investment has a direct relationship with tax collection, spending on education (measured as spending per student in higher education) and economic growth, in addition to also having a negative relationship with the level of unemployment in Peru, during the period 2017 - 2019.